Work Ambiguitas Dan Support Leader Terhadap Kinerja Karyawan Indihome Kota Semarang - Yuyun Ristianawati; Anis Turmudhi (Universitas Ngudi Waluyo, 2020)
The purpose of this study was to determine the effect of job ambiguity on employee performance in Indihome City of Semarang, to determine the effect of leadership support on employee performance in Indihome City Semarang, and to determine the effect of job ambiguity and leadership support on employee performance in Indihome Semarang City. In this study the population to be studied is 112 Indihome City Semarang customers.